Efficacy of Different Statins Among Newly Diagnosed Dyslipidemic Patients in Dhulikhel Hospital - Humagain, Sanjaya; Pathak, Surya Raj; Koju, Rajendra Prasad (Nepalese Heart Journal, 2023)
Background and Aims: Cardiovascular Disease is the leading cause of death. Prevention of cardiovascular disease is the major aim of treatment of anyone who has risk. Dyslipidemia lies in the center of cardiovascular disease risk. Not only there is difference in pattern of dyslipidemia and response to statins in different ethnic groups, there is difference in mortality due to cardiovascular disease in different race and ethnic group. Atorvastatin and Rosuvastatin are the first line statins. This study is carried out to see how our population responds to these statins in terms of change in lipid profile. Methods: It is a real world observational study. Dyslipidemia patients requiring statins were given either Atorvastatin 10 mg or Rosuvastatin 5 mg according to physician’s discretion. Demographic profile and baseline lipid was recorded. Lipid profile was again recorded after 3 to 4 months of treatment. Result: Out of 343 enrolled only 304 data was analyzed. Total cholesterol decreased by 21.9 % (p = 0.002) in Atorvastatin group and by 22.9 % (p= 0.002) in Rosuvastatin group. Low Density Lipoprotein (LDL) decreased by 22.3 % (p = 0.004) in Atorvastatin group and 21.5% (p=0.005) in Rosuvastatin group. There was no significant difference between two groups. Conclusion: Both Atorvastatin 10 mg and Rosuvastatin 5 mg can reduce the lipids significantly in our population. There is no difference in using Atorvastatin 10 mg or Rosuvastatin 5 mg. However, reduction was only mild to moderate with the given doses.